Tindak Tutur Ilokusi pada Podcast “Supaya Sembuh dari Trauma” oleh Raditya Dika dan dr. Jiemi Ardian : Penelitian - Eka Dwi Sasmita Putri; Nurfalida; Haura Zhafira Nur Azizah; Dodi Firmansyah; Dase Erwin Juansah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the form and function of illocutionary speech acts in the podcast "Supaya Sembuh dari Trauma," hosted by Raditya Dika and Dr. Jiemi Ardian. The focus of this research is to understand how language plays a role as a therapeutic communication medium in the trauma recovery process. The research method used was a qualitative descriptive approach. Data were obtained through listening and note-taking of the utterances in the podcast conversations, then analyzed using Searle's speech act theory, which includes five categories: assertive, directive, expressive, commissive, and declarative. The analysis revealed nine utterances containing illocutionary elements: two assertive utterances that function to convey information, three directive utterances that serve to request or inquire, two expressive utterances that indicate the speaker's feelings, one commissive utterance containing a statement of commitment, and one declarative utterance that establishes a decision. These findings indicate that directive and assertive speech acts are the most dominant forms because they play a role in building empathy, conveying education, and encouraging listener engagement. Thus, the use of language in this podcast not only serves as an informative tool but also has social and psychological dimensions that support the communicative healing process of trauma.